Effects of variable and constant domains on physicochemical properties and secretion of mouse-chicken chimeric IgY, human IgG1, and IgE antibodies - 최주호 (The Graduate School, Ajou University, 2024)
The variable (V) and constant (C) regions of antibodies mutually affect their structures, which in turn influence their affinity, and specificity. The consequences of C-region switching between mammalian and evolutionarily distinct avian antibodies and the impact of V-region absence on antibody secretion remain unknown. Most studies have focused on IgG secretion, while other isotypes, particularly IgE, are less understood. In this study, I constructed mouse-human and mouse-chicken chimeric antibodies, as well as V region-deletion or alteration mutants. These antibodies were assessed for their physicochemical properties and secretion process in HEK293 cells. Physicochemical properties of chimeric antibodies depended on the V and C region combination. The absence of VH or VL domain did not affect expression and secretion of mutant IgGs. An aberrant pseudo Vκ (ψVκ) domain hindered antibody secretion, distorted light chain (LC) structure, decreased its stability. In the absence of heavy-light interchain disulfides, Cκ allowed individual secretion of its cognate heavy chain (HC) of IgG. Unlike IgG, the absence of VH or VL domains blocked IgE secretion. V domains are not critical for IgG expression, assembly, and secretion, but are crucial for IgE secretion. An intact VL domain is essential for LC or assembled IgG secretion. These findings provide valuable insights for designing various types of antibody molecules with improved properties and secretion efficiency.
학위논문(박사)--의생명과학과,2024. 8
Keywords: IgE; IgG; Variable region; antibodies; assembly; constant region; expression; physicochemical properties; secretion